Synthesis of Peptide–Adenine Conjugates as a New Tool for Monitoring Protease Activity. Issue 1 (11th December 2018) - Masurier, Nicolas; Soualmia, Feryel; Sanchez, Pierre; Lefort, Valérie; Roué, Mia; Maillard, Ludovic T.; Subra, Gilles; Percot, Aline; El Amri, Chahrazade
Abstract : We took advantage of the powerful adenine SERS (Surface Enhanced Raman Spectroscopy) probe to design peptide–adenine conjugates as candidates for use as serine protease substrates. Whereas the direct introduction of the peptide sequence on the adenine exocyclic N6 amine gave an imidazopurinone derivative, the introduction of an aminoethyl linker between the adenine group and the peptide chain led to the expected candidate probes. These potential substrates were then evaluated for monitoring the hydrolytic activity of trypsin, used as a model protease, by HPLC and by SERS. We demonstrated that the Boc–VPR–adenine conjugate is a substrate of trypsin and constitutes a good starting point to design optimized substrates to monitor protease activity by SERS. Abstract : We report an efficient way to synthesize challenging peptide–adenine conjugates as alternative to the aminomethylcoumarine (AMC)‐serine protease substrates.